2021
DOI: 10.1039/d0ra07971e
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and BET family proteins as epigenetic targets in cancer therapy: their degradation, present drugs, and possible PROTACs

Abstract: Alteration in the pattern of epigenetic marking leads to cancer, neurological disorders, inflammatory problems etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 251 publications
(314 reference statements)
0
4
0
Order By: Relevance
“…In reports on BRD biology, it has been shown that cancer is induced when the transcriptional regulation of genes encoding BRD proteins is unregulated and the transcriptional program of related transcription factors is abnormally driven. , Therefore, research on BRD target-based therapeutic strategies is necessary. Leukemia and malignant tumors, such as prostate cancer, malignant melanoma (MM), breast cancer, lymphoma, lung cancer, colon cancer, AML, and neuroblastoma, are susceptible to the aforementioned inhibitors.…”
Section: Application Of Brd-containing Hat Inhibitors In Human Diseasesmentioning
confidence: 99%
“…In reports on BRD biology, it has been shown that cancer is induced when the transcriptional regulation of genes encoding BRD proteins is unregulated and the transcriptional program of related transcription factors is abnormally driven. , Therefore, research on BRD target-based therapeutic strategies is necessary. Leukemia and malignant tumors, such as prostate cancer, malignant melanoma (MM), breast cancer, lymphoma, lung cancer, colon cancer, AML, and neuroblastoma, are susceptible to the aforementioned inhibitors.…”
Section: Application Of Brd-containing Hat Inhibitors In Human Diseasesmentioning
confidence: 99%
“…BRD9 is the BRD-containing subunit of the BAF (BRG-/BRM-associated factor) and its close homolog BRD7 is the subunit of PBAF (polybromo-associated BAF) 26 , 27 . BAF and PBAF are two variants of the SWI/SNF complex, which regulate gene expression, DNA replication, and DNA repair 28 , 29 . Overexpression of BRD7/9 can lead to cancers development.…”
Section: Introductionmentioning
confidence: 99%
“…[16] This family of protein over the years have been a therapeutic target for several diseases such as cancer and inflammation. [17,18] BET proteins are characterized by dual bromodomains (BD1 and BD2) such as BRD2, BRD3, BRD4, and BRDT. BETs are known to bind the acetylated lysine on histone complexes of proteins to promote recruitment and stabilization, a rate-limiting step in gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The Bromodomain and extra‐terminal domain (BET) protein family consists of a group of proteins that specializes in recognizing acetylated lysine on chromatin [16] . This family of protein over the years have been a therapeutic target for several diseases such as cancer and inflammation [17,18] . BET proteins are characterized by dual bromodomains (BD1 and BD2) such as BRD2, BRD3, BRD4, and BRDT.…”
Section: Introductionmentioning
confidence: 99%